Asset-Based Community Development dalam Penguatan Sustainable Agriculture melalui Intensifikasi dan Peningkatan Kapasitas Sumber Daya pada Program Tawangargo Smart Eco-Farming Village (TAMENG) - Kadek Ardhika Widya Kresna; Edwyk Sony Udaieby; Adi Candra Purnama; Muhammad Riefqi Putra Juliesa; Amellya Putri Kaharu (ijd-demos, 2026)
Abstract This study analyzes the effectiveness of sustainable intensification strategies and human resource capacity building through the Tawangargo Smart-Eco Farming Village (TAMENG) Program within the framework of Sustainable Agriculture. Facing the challenges of the Triple Planetary Crisis, the transformation of horticulture in Tawangargo Village is carried out by optimizing the community's internal strengths. Using a descriptive qualitative method, data were collected through interviews, observation, and documentation studies, employing purposive and snowball sampling techniques. The results show that the integration of sustainable agriculture with the Asset-Based Community Development (ABCD) approach successfully shifts the development paradigm from a needs-based to an asset-based approach. This program transforms farmers into primary subjects and innovators within a living lab ecosystem. Ecologically, the program restores ecosystem health through soil restoration and systemic waste management. Economically, land productivity and the welfare of farm laborers have significantly increased. The success of this social investment proves the creation of an autonomous, resilient, and adaptive agricultural system against the global climate crisis. Keywords: asset-based community development (ABCD), sustainable agriculture, TAMENG program, regenerative agriculture.   Abstrak Penelitian ini menganalisis efektivitas strategi intensifikasi berkelanjutan dan penguatan kapasitas SDM melalui Program Tawangargo Smart-Eco Farming Village (TAMENG) dalam kerangka Sustainable Agriculture. Menghadapi tantangan Triple Planetary Crisis, transformasi hortikultura di Desa Tawangargo dilakukan dengan mengoptimalkan kekuatan internal masyarakat. Menggunakan metode kualitatif deskriptif, data dikumpulkan melalui wawancara, observasi, dan studi dokumentasi dengan teknik purposive serta snowball sampling. Hasil penelitian menunjukkan bahwa integrasi pertanian berkelanjutan dengan pendekatan Asset-Based Community Development (ABCD) berhasil mengubah paradigma pembangunan dari berbasis kebutuhan menjadi berbasis aset. Program ini mentransformasi petani menjadi subjek utama dan inovator dalam ekosistem living lab. Secara ekologis, program ini memulihkan kesehatan ekosistem lewat restorasi tanah dan pengelolaan limbah sistemik. Secara ekonomi, produktivitas lahan dan kesejahteraan buruh tani meningkat signifikan. Keberhasilan investasi sosial ini membuktikan terciptanya sistem pertanian otonom, tangguh, dan adaptif terhadap krisis iklim global. Kata kunci: asset-based community development (ABCD), sustainable agriculture, program TAMENG, pertanian regeneratif.